Revisiting the Chemistry of Superoxide: Its Roles in Organic Synthesis - Budanur, Basavaraj M.; Mahadevegowda, Surendra H.; Bhat, Chinmay; Khan, Faiz Ahmed (Synthesis, 2025)
This review offers a comprehensive survey of the diverse chemical reactivity of the superoxide ion (O₂•−) in the context of organic synthesis. As a reactive oxygen species with both radical and anionic character, superoxide demonstrates remarkable versatility—acting as a Brønsted base, a nucleophile, an oxidant, and a reductant. Drawing on reported experimental and theoretical studies, we examine its roles across a range of transformations, highlighting how its reactivity varies with substrate structure and reaction medium. Special attention is given to mechanistic pathways and solvent effects, and the distinctive features of superoxide-mediated reactions compared to those involving alternative reagents. By consolidating and analyzing scattered findings from the literature, this review aims to provide a valuable reference for researchers exploring the synthetic potential of superoxide chemistry in both academic and industrial contexts.
Keywords: Reduction; Oxidation; Nucleophiles; Free radicals; Regioselectivity